An Analysis of the Southern Gothic Genre in William Faulkner’s “A Rose for Emily” - Muhlisin, Muhlisin; Aprianto, Dedi (J-Lalite: Journal of English Studies, 2025)
This study analyzes the Southern Gothic genre in Faulkner’s “A Rose for Emily.” This study is developed based on the gaps in several previous studies, which primarily emphasized the structure and narrative impacts on readers’ comprehension, the values and societal structure, Faulkner’s linguistic choice, Emily’s contrasting identity, and the psychological factors that influenced Emily’s behavior. This study aims to identify the Southern Gothic elements, themes, and symbols in “A Rose for Emily” based on Smith’s, Harris’, and Lloyd-Smith’s concepts of Southern Gothic literature. This qualitative study employs a textual analysis method with a close reading approach. The primary data for this study is a short story entitled “A Rose for Emily.” The data was collected through a series of steps and then subjected to analysis and interpretation. The findings demonstrate that the short story incorporates a range of Southern Gothic elements, including depictions of environmental decay, horror, and the exploration of mental illness. The reflection of thematic elements of Southern Gothic is in Emily’s isolation and seclusion, Emily’s resistance to the changes, death, and the macabre. Ultimately, certain symbols are reflected, such as Emily’s house representing the grotesque, the dust and arsenic symbolizing death, the unpleasant smell representing the decaying life of Emily, and the color of the rose symbolizing her tragic and unrealistic love. This study can contribute to a broader understanding of Southern Gothic literature and how Faulkner portrays the elements of the Gothic in his work. In conclusion, this short story is an example of a Gothic tale, as it is replete with elements of Gothic tradition, themes, and symbols.